2019
DOI: 10.1111/jcmm.14328
|View full text |Cite
|
Sign up to set email alerts
|

Machine‐learning based radiogenomics analysis of MRI features and metagenes in glioblastoma multiforme patients with different survival time

Abstract: Background This study aimed to examine multi‐dimensional MRI features’ predictability on survival outcome and associations with differentially expressed Genes ( RNA Sequencing) in groups of glioblastoma multiforme ( GBM ) patients. Methods Radiomics features were extracted from segmented lesions of T2‐ FLAIR MRI data of 137 GBM patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Using 84 patients’ TCGA data as validation cohort (and Chinese Glioma Genome Atlas—CGGA as training set), the same group [29] have performed a radiogenomic analysis showing the ability of radiomic features to predict progression-free survival and their association with the immune response, programmed cell death, cell proliferation, and vasculature development, as reported by transcriptomic data. Liao et al [30], using a machine learning approach on data from 46 patients, showed high or moderate correlations between differential expression of three patterns of gene expression—also defined metagenes ( TIMP1 , ROS1 , EREG ) and image features. In particular, EREG was found positively associated with dependence non-uniformity, difference average, contrast, and cluster prominence.…”
Section: Resultsmentioning
confidence: 99%
“…Using 84 patients’ TCGA data as validation cohort (and Chinese Glioma Genome Atlas—CGGA as training set), the same group [29] have performed a radiogenomic analysis showing the ability of radiomic features to predict progression-free survival and their association with the immune response, programmed cell death, cell proliferation, and vasculature development, as reported by transcriptomic data. Liao et al [30], using a machine learning approach on data from 46 patients, showed high or moderate correlations between differential expression of three patterns of gene expression—also defined metagenes ( TIMP1 , ROS1 , EREG ) and image features. In particular, EREG was found positively associated with dependence non-uniformity, difference average, contrast, and cluster prominence.…”
Section: Resultsmentioning
confidence: 99%
“…It is able to transform the images into analyzable statistics with mathematical calculation, which could be further applied in machine learning technology. This set of methods has been widely explored in clinical diagnosis, tumor grading, treatment prediction, and survival prediction by previous researchers (16,(22)(23)(24)(25)(26)(27). For example, the study applying RF classifier in the discrimination between primary central nervous system lymphoma and atypical glioblastoma represented satisfactory diagnostic ability with AUC of 0.921 (27).…”
Section: Discussionmentioning
confidence: 99%
“…Radiomic features were calculated from the VOIs using Olea Sphere software. A total of 92 texture features were collected: 19 first-order metrics, including the mean, standard deviation, skewness, and kurtosis, and 73 second-order metrics consisting of 23 gray level run length matrix [41], 16 gray level run length matrix [42], 15 gray level size zone matrix [43], five neighboring gray tone difference matrix [44], and 14 gray level dependence matrix [45]. Definitions and calculations of these features are explained elsewhere [46].…”
Section: Volume Acquisition and Texture Analysismentioning
confidence: 99%